Rehabilitative and infiltrative treatment with hyaluronic acid inelderly patients with rotator cuff tears - Costantino, C.; Olvirri, S. (Acta Biomedica Atenei Parmensis, 2009)
Rotator cuff tears are an important cause of disability. It is frequently observed in elderly people with a consequent loss of autonomy in daily life activities. The aim of this study is to evaluate the efficacy of the infiltrative treatment with hyaluronic acid, followed by a selective rehabilitative programme in elderly patients who do not present indications for surgical treatment. Twenty-two patients were selected (14 men and 8 women), ranging from 70 to 89 years, (mean age 78.1) with rotator cuff tears. They underwent to a conservative treatment consisting in a series of 3 infiltrations (once a week) with hyaluronic acid (jointex starter molecular weight: 800-1200 kdalton) followed by a specific rehabilitative treatment (passive and active assisted kinesitherapy). Each patient was evaluated for pain through a Visual Analogic Scale (V.A.S.). Costant Murley and the Shoulder Rating Questionnairev were adopted to analyze the loss of range of motion of the shoulder as well as autonomy in daily life activities. The obtained results were statistically significant (p<0,0005), both for the reduction of pain and for the improvement of range of motion and autonomy in daily life activities. The encouraging results obtained with this treatment could be considered as a valid choice instead of a surgical treatment in selected cases.